Integración de la migración venezolana en Perú: Un análisis para la provisión de servicios básicos - Lizarzaburu Bolaños, Edmundo (2024)
Peru has become a host country for the migration of Venezuelan citizens, and this implies that the government issues responses within the framework of the search for socioeconomic integration and the expansion of public services. The current needs of Venezuelan citizen migration must be analyzed by society and by the various levels of government, not only in the short term, but also in the medium and long term, based on information from primary and secondary sources. It is estimated that more than 500 thousand new Peruvians with Venezuelan family ties will exist in a period of approximately 5 years. It is estimated that more than 2 billion soles are needed for education alone to meet this new demand. The objective of this article is to show the potential gap in attention in public services, a product of the migration that has occurred from 2019 to 2023. It is argued, given the birth of new Peruvian citizens, that it is time for the State to welcome them and provide them with all the necessary services for their full development, and that in the face of the migration emergency, the attention of the authorities and cooperating organizations is required in the short term. Understanding future social spaces could improve the capacities necessary to face poverty, social instability, and the vulnerability of Venezuelan migrant families, whose children born in Peru will make up a new group of first-generation Peruvians.